KEBERADAAN BATIK KEDIRI JAWA TIMUR - M. Mujiono; D. Dharsono (Institut Seni Indonesia Surakarta, 2015)
The article entitled â€œKeberadaan Batik Kediri Jawa Timurâ€ (The Existence of Batik Kediri East Java) coversthe appearance and the development of batik in Kediri Residence. The analysis result uses qualitativemethod. Theories concerning culture and history are used to solve problems of the existence and characteristicsof batik Kediri in relation to the presence and the activities of batik making in Kediri through the culturalapproach, aesthetic approach by AAM, and Djelantik is applied to analyze the forms of batik Kediri motives.Analysis process is executed in two steps covering interactive and interpretative developed by Miles andHuberman. The characteristics of batik Kediri can be reviewed from the shape and the structure of batik withthe technique of natural and synthetic coloring. The values contained in batik Kediri show the condition ofKediri area. It can be seen from the several forms of batik pattern and motive made by batik maker in Kediri.The aesthetics of batik Kediri can be seen and felt from the pattern of tourism and local culture, abstractpattern, the creative pattern of natural suggestion, classic pattern, and the unity of classic pattern andnatural suggestion.Keywords: batik, aesthetics, motive, Kediri